Integrasi Sikap dan Kepuasan Kerja: Sebuah Meta Analisis tentang Peran Krusial Sikap Kerja dalam Kesuksesan Organisasi Modern - Purnama Asri, Cahya (Atma Workshop Innovation, 2025)
This research explores the integration of attitude and job satisfaction in modern organizations. Attitude in the context of work is defined and explored using theories Attitude Consistency Theory. Additionally, the study delves into the concept of job satisfaction, detailing its definition, dimensions, and theories such as Herzberg's theory and Edwin Locke's job satisfaction model. The research examines the dynamic interaction between employee attitudes and job satisfaction and its implications for organizational performance. Finally, the study looks at the impact of rapid changes, such as remote work and technology, on attitudes and job satisfaction, providing practical recommendations for managing human resources in the current work environment. Overall, the research emphasizes the importance of integrating attitude and job satisfaction to create a positive work culture and enhance organizational performance in the dynamic business era.